Subacute exposure to apigenin induces changes in protein synthesis in the liver of Swiss mice - Jarosz, Łukasz S.; Socała, Katarzyna; Michalak, Katarzyna; Bulak, Kamila; Ciszewski, Artur; Marek, Agnieszka; Grądzki, Zbigniew; Wlaź, Piotr; Kowalczuk-Vasilev, Edyta; Rysiak, Anna (Frontiers in Physiology, 2025)
Apigenin is a natural flavonoid with various pharmacological properties. Available data indicate that it affects the metabolic processes and protein profile of cells, including hepatocytes. However, there is speculation that the use of apigenin may have a hepatotoxic effect. The aim of the experiment was to assess the effect of apigenin administered intraperitoneally to mice on the concentrations of pro- and anti-inflammatory cytokines in the liver tissue and to analyse liver weight and morphological changes in the liver parenchyma. A proteomic analysis was also performed to examine differences in genes expression for specific proteins in liver cells. Adult male albino Swiss mice were divided into two groups and treated with either apigenin (50 mg/kg BW) – APG, or a vehicle (1% DMSO) – CONT, every 24 h for 14 days. The material for the study consisted of liver samples. Slight hepatocyte degeneration microscopically were demonstrated in most mice exposed to apigenin. No significant differences were observed in the absolute and relative weight of the liver or the concentrations of pro- and anti-inflammatory cytokines between the control and experimental group. The mass spectrometry results indicate significantly higher synthesis of the proteins MAP2K19, CEP69, GNMT, BPIFA3, SYT17, ANKRD1, GRHPR, CLEC1A and EF2 in the livers of mice from the APG group in comparison to CONT group. Exposure of mice to apigenin induces functional changes in the liver. In conjunction with the microscopical and proteomic analyses, this study may indicate that inflammatory changes developing in the liver could be self-limiting and subject to regenerative processes.